Prepare : Workbook - Jones Gareth (Cambridge University Press, 2015)
The book is an active 7-step general course that combines comprehensive Cambridge English test preparation for schools. This multifaceted course brings together all the tools and technologies you'd expect to get the results you want. Whether you are teaching general English or focusing on exams, get ready. Prepare well for what's to come, including real life and real Cambridge English exams. Cambridge English Prep Level 1: Student books engage students and build vocabulary with age-appropriate topics. Its unique approach builds on cutting-edge language research from English Profile and Cambridge Learner Corpus. The Preparation section develops your writing and speaking skills. Student books and online workbooks are also available separately